Application of Environmental Learning Learning Strategies to Increasing Science Learning in MI/SD in View of Children's Gender - Rabiatul Adawiyah Batubara (Journal of Contemporary Gender and Child Studies, 2022)
Environmental learning strategies include the surrounding environment and students can easily master the material through observation. In this learning strategy students are required to be able to learn to love and be able to apply the learning of the surrounding environment to themselves and without coercion from anyone. The task of the teacher in this case, is to strive for this learning strategy to look fun and not boring for students. The research method used in this study is qualitative research. This research method usually uses data collection techniques consisting of observations, interviews and documentation studies. Through the Environmental Learning strategy, students can understand learning when outside the classroom and are also able to make the enthusiasm of learning students' motivation higher, because students experience a different learning atmosphere than usual.